Excellent yellow emission of Si3N4:Eu nanorods derived from waster silicon with better thermal stability for white LEDs. Issue 1 (1st January 2023) - Ge, Wanyin; Yin, Honglei; Lu, Chenhui; Zhang, Xinmeng; Song, Panpan; Ma, Mingsheng; Liu, Zhifu; Tian, Ye
Abstract: The core issue of light emitting diodes (LEDs) for actual application is the thermal stability of phosphors. Silicon nitride (Si3 N4 ) is generally recognized as especially important structural material due to its excellent mechanical properties at extreme high temperature. In this work, Si3 N4 : Eu was demonstrated to be an excellent luminescence functional material for LEDs. The discarded corner-waster silicon raw material was utilized to act as the precursor. The Si3 N4 :Eu phosphor was synthesized by a facile nitriding process at elevated temperature. The pure α-Si3 N4 :Eu nanorods were successfully obtained by adjusting the doping concentration of Eu. It is coexistence with mixed-valence (divalent and trivalent) for Eu in α-Si3 N4 according to X-ray photoelectron spectroscopy. The synthesized α-Si3 N4 :Eu nanorods showed bright yellow under the excitation of 365 nm (UV) and white luminescence by 460 nm chip (Blue). The Si3 N4 :Eu nanorods possess excellent thermal stability, maintains nearly 70% of the origin intensity even at temperatures over 300 °C. The Si3 N4 :Eu nanorods demonstrated comparable performance to commercial YAG:Ce 3+ (YAG). Moreover, the long-term thermal stability of Si3 N4 :Eu nanorods is superior to commercial YAG, revealing the enhanced service performance. This work not only presents a facile Si3 N4 :Eu nanorods green synthesis route from waste utilization, but also offers an enhanced service performance for the high temperature LEDs application.